The effect of motivational interviewing on patients with early post-stroke depression: a quasi-experimental study - Yingjie Fu; Yi Zhang; Qianying Deng; Yuenv Wang; Siyi Su; Zheng Wang; Luyi Xu; Beibei Lin; Yun Li; Jufang Li (BMC Psychiatry)
Abstract Background Post-stroke depression (PSD) constitutes an important complication of stroke, affecting approximately one-third of stroke patients. PSD decreases rehabilitation motivation, delays function recovery, and increases the family and social burden of stroke patients. Motivational interviewing (MI) may be an effective and practical intervention strategy, but its effectiveness in improving PSD remains uncertain. Methods A parallel two-group quasi-experimental study was conducted. Patients with early PSD were recruited from the neurology department of a hospital in southeast China and were allocated to the control group and intervention group by wards. Patients in the intervention group received one session of face-to-face motivational interviewing and three sessions of telephone motivational interviewing, while patients in the control group received routine nursing and follow-up of the neurology department. Outcomes including depression, sleep quality, and quality of life were evaluated at baseline (T0), after intervention immediately (T1) and three months after intervention (T2). Descriptive statistics, t-test, Mann-Whitney U test, Wilcoxon signed rank sum test and generalized estimating equation were used to analyze data. Results There were no significant differences in patients’ sociodemographic and clinical information between the intervention and control groups at baseline. The scores for depression were statistically different between the two groups (Z=-5.757, p < 0.001) at T1 and T2 (t=-7.964, p < 0.001). The scores for sleep quality were statistically different between the two groups at T1 (Z=-2.840, p = 0.005). The result of the generalized estimating equation modeling analyses indicated that interaction effects were statistically significant in depression and sleep quality scores. The intervention group showed a significantly higher rate of decrease in the depression score from T0 to T1 (95% CI: -11.227 to -7.748, p < 0.001) and T0 to T2 (95% CI: -11.683, -6.170, p < 0.001), compared with the control group; the intervention group had a greater reduction in the sleep score from T0 to T1 (95% CI: -2.502 to -0.962, p < 0.001), compared with the control group. Conclusions MI could effectively improve depression and sleep quality in patients with early PSD. However, MI failed to improve quality of life in patients with early PSD. These findings provide a foundation for future large-scale randomized controlled trials to further evaluate the efficacy of MI in patients with early PSD. Trial registration Retrospectively Registered, Chinese Clinical Trial Registry ( http://www.chictr.org.cn || ChiCTR2200064386|| Registration Date: 2022/10/06).